BEYOND BUDGETING IMPLEMENTING - Yati Nurhajati (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2015)
ABSTRACT: Budgeting traditional organizational models that have been developed in the 1920s to help control the costs of financial managers in largeorganizations such as Dupont, General Motors, ICI and Siemens. The model has been designed to carry out an approach to the production of lead in the business. Large organizations cope with the placement activity increases the complexity of each different product lines, regions, or technologies into a compartment that is set, as a business unit or division, and all compartments subject to financial discipline of a strong company organizing.The underlying thread traditional model of budgeting is in control. The mission statement approved by senior executives who have been translated into strategic planning with planner and forward it to the hierarchy of operational managers, who prepare their budget. Once the plan and budget has been approved, all of which have demanded the manager is loyalty to that plan. Because the central office does not like surprises, control reports constantly fed back on a line. If the report shows its achievements were veering off -track, a new directive was issued from headquarters.